Land Use Cover Change and Hotspots Identification of Upper Meghna River Basin, India - Bora, Amritee; Walia, Devesh; Mipun, B.S. (Indian Forester, 2023)
River basins always play a vital role in human habitation. Talking about land use cover, consideration of river basins is one of the most impotent aspects of land use study in terms of sustainable use of land resources. River Meghna is a transboundary river shared by India and Bangladesh. However, regarding the basin area of the river, a small portion o f the basin also comes under Myanmar. The total geographical area of the basin is 82,000 Km2 including 29 transboundary sub-basins. Hydroiogically India shares a part of the Upper Meghna basin, habited by less than 10 mlillon indigenous populations, spread over six northeastern states of India. It has been noticed that the topography of the region and the demographical structure together has a particular impact on the land use pattern of the region, where some land areas are undergoing periodically repeated land use change. The primary aim of the present study is to identify the hotspots of land use/cover change (LUCC) of the basin area based on the frequency of change in six (6) different time frames from 2005 to 2019 and further to assess the rate of land use/cover change (LUCC) of the region by calculating annual land use change rate (ALUCR) within the study period.